A novel modified-curcumin 2.24 suppresses MMPs in a periodontal-relevant cell culture model: a pilot study - Isabella Ho; Cindy Leung; Nidhi Bhandari; Hsi-Ming Lee; Lorne M. Golub; Francis Johnson; Ying Gu (Frontiers in Oral Health, 2026)
Background Matrix metalloproteinases (MMPs) play critical roles in periodontal tissue destruction. The present study evaluated the efficacy of a novel chemically modified curcumin 2.24 (CMC 2.24) in reducing MMP levels, activity, and its activation, in a periodontal relevant cell culture model involving human mononuclear THP-1 cells. In addition, the p38 mitogen-activated protein kinase (p38 MAPK) signaling pathway played a key role in the inflammatory process in response to various stimuli such as cytokines, bacterial antigens, and endotoxin lipopolysaccharide (LPS). Therefore, the effect of CMC 2.24 on p38 MAPK levels was evaluated as well. Methods THP-1 monocytes were cultured and stimulated with LPS in the presence or absence of 5 µM CMC 2.24, Chemically modified tetracycline 3 (CMT-3), or doxycycline for 6 or 18 h. Conditioned media (CM) were analyzed for MMP-9 and collagenase levels using gelatin and collagen zymography. In addition, LPS-treated CM were incubated with 4-Aminophenylmercuric acetate (APMA) in the presence or absence of the above agents for an hour. MMP activation was evaluated by gelatin zymography. THP-1 MMP enzyme activity was analyzed using a fluorogenic substrate. p38 MAPK levels in THP-1 cell lysates were determined using the western blot technique. Results CMC 2.24 significantly reduced elevated MMP-9 and collagenase levels compared to LPS controls. CMC 2.24 also inhibited APMA-induced activation of MMP-9 and reduced MMP enzymatic activity. Further, CMC 2.24 significantly suppressed p38 MAPK levels, whereas CMT-3 and doxycycline showed limited or no effect. Conclusions CMC 2.24 functions as a highly pleiotropic inhibitor, acting at multiple regulatory levels: reducing MMP levels, activation, and enzymatic activity, while also downregulating MAPK signaling. These findings highlight CMC 2.24 as a promising therapeutic candidate for the modulation of inflammation-associated matrix degradation in chronic inflammatory diseases such as periodontitis.